Customer Loyalty and Brand Management - Rubio, Natalia (MDPI - Multidisciplinary Digital Publishing Institute, 2019)
Loyalty is one of the main assets of a brand. In today's markets, achieving and maintaining loyal customers has become an increasingly complex challenge for brands due to the widespread acceptance and adoption of diverse technologies by which customers communicate with brands. Customers use different channels (physical, web, apps, social media) to seek information about a brand, communicate with it, chat about the brand and purchase its products. Firms are thus continuously changing and adapting their processes to provide customers with agile communication channels and coherent, integrated brand experiences through the different channels in which customers are present. In this context, understanding how brand management can improve value co-creation and multichannel experience-among other issues-and contribute to improving a brand's portfolio of loyal customers constitutes an area of special interest for academics and marketing professionals. This Special Issue explores new areas of customer loyalty and brand management, providing new insights into the field. Both concepts have evolved over the last decade to encompass such concepts and practices as brand image, experiences, multichannel context, multimedia platforms and value co-creation, as well as relational variables such as trust, engagement and identification (among others).